2005
DOI: 10.2304/eerj.2005.4.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Migrants' Resources: Multilingualism and Transnational Mobility. A Study on Learning Paths and School to Job Transition of Young Portuguese Migrants

Abstract: In this contribution, the results of an empirical study on young immigrants' learning paths and school to job transition are presented. The study focused on the strategies of successful students from the Portuguese immigrant minority in Hamburg. One aim was to find out whether the young people could profit by their migration experiences and multilingual skills. Increasing the multilingualism of individuals is an official goal of the European Union, and it is predicted that the labour market will give increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
0
12
0
2
Order By: Relevance
“…In the European context, Fürstenau () studied the strategies used by young people of immigrant backgrounds to position themselves in the transnational fields of education and the labor market. Based on an interview study with 27 young people from Portuguese immigrant families in Hamburg, Germany, who had completed secondary schooling and were planning a school‐to‐work transition or further education, Fürstenau found that the young people were informed about educational and career options in Portugal through their family and social networks and were able to describe the relative advantages of vocational paths in Germany and Portugal in planning their careers.…”
Section: Literacy Practices In Transnational Migrant Families and Commentioning
confidence: 99%
See 1 more Smart Citation
“…In the European context, Fürstenau () studied the strategies used by young people of immigrant backgrounds to position themselves in the transnational fields of education and the labor market. Based on an interview study with 27 young people from Portuguese immigrant families in Hamburg, Germany, who had completed secondary schooling and were planning a school‐to‐work transition or further education, Fürstenau found that the young people were informed about educational and career options in Portugal through their family and social networks and were able to describe the relative advantages of vocational paths in Germany and Portugal in planning their careers.…”
Section: Literacy Practices In Transnational Migrant Families and Commentioning
confidence: 99%
“…It is important to note that transnational mobility in the diverse social fields documented in these studies has to be understood with regard to larger structural forces that affect possibilities of movement in these fields. The relative freedom of mobility among the young adults documented in Fürstenau's () study and the potential for the youths’ multilingual literacies to translate into value in their careers are dependent on structural policies at both the panregional level of the European Union and its member states as well as the youths’ status as legal citizens of the European Union. These political conditions stand in contrast to those faced by undocumented immigrants and are experienced differently by racially and religiously stigmatized immigrants, especially in the context of growing antiimmigrant sentiments and enacted policies in many countries.…”
Section: Literacy Practices In Transnational Migrant Families and Commentioning
confidence: 99%
“…The researchers highlight the role of English in the world and summarize "the (positive and negative) effects of globalization on English language teaching" (Alfehaid, 2014). The questions of "increasing the multilingualism of individuals" as an ostensible purpose of the European Union have been also discussed, and the fact that "the labour market will give increasing importance to the ability to communicate and work in contexts of linguistic and cultural diversity" is predicted (Fürstenau, 2005).…”
Section: Competence In English As a Necessary Requirement For Studentmentioning
confidence: 99%
“…There are different thoughts about the empirical, ideological and methodological dimensions of the globalization, pluralization, localization of English. Some of them are that "migrationbased language pluralism and globalized forms of identity conflict pose challenges for both ethnographic educational research and linguistic anthropology" (Collins, 2007); considering whether "students from immigrant minority" can benefit from acquiring multilingual skills (Fürstenau, 2005); or how much and in which way teaching English has been influenced by globalization (Alfehaid, 2014).…”
Section: Competence In English As a Necessary Requirement For Studentmentioning
confidence: 99%
“…The family network described here shares a knowledge of the entrance conditions and the course of study in this Studienkolleg, and this knowledge functions as an orientation for newcomers. The pattern outlined here can be viewed as a socially institutionalized trajectory (Fürstenau, 2005). It is shaped by migration and educational regimes as well as by social structures and institutions, which together determine a social field that channels individual decisions and strategies.…”
Section: Migration and Educational Regimesmentioning
confidence: 99%